Lembaga keuangan syariah di Indonesia - Zidna, Muhammad Hifdhul Islam Qur’any; Az-zahid, Muhammad Hanif (Maliki Interdisciplinary Journal, 2024)
Sharia Financial Institutions. The Islamic economic system cannot be separated from banking and financial institutions. Financial institutions are an identity in an economic system and are a means of enforcing the rules in the economic system itself. Even though traditional banking has become an important part of the economy, there are still many scholars who argue that the interest obtained from banking transactions is not in accordance with Islamic teachings. Therefore, financial institutions with an Islamic concept emerged which could be known as sharia banking, but in reality many users of sharia banking services also came from non-Islamic groups. Financial institutions are a major part of the modern economy that serves the public who use financial services. With the support of financial institutions, economic actors can carry out large-scale financial transactions that cannot be done with cash.